Untrained Teachers, Unequal Learning Opportunities: Investigating the Relationship between Teacher Preparation and Children’s Educational Progress in Pakistan” - Anila Hussain (Journal for Social Science Archives, 2025)
The quality of teachers is an essential factor determining education outcomes, especially in developing countries where there is inequality in teacher preparation leading to inequality in the learning process of students. Teacher preparation is a persistent challenge in developing nations such as Pakistan where disparity in teacher preparation continues to hamper the educational achievements of children. This study evaluates the impact of teacher preparation on learning outcomes through the analysis of secondary data collected through the SABER Service Delivery Survey – Pakistan from the World Bank. The quantitative research approach is employed in this study where the data of 19,003 students is analyzed through associating student achievement with school-level teacher preparation variables such as teacher training, teacher education, teacher knowledge, and teacher attributes. It was found out that teacher preparation variables have significant relationships with learning outcomes of children. There are significant positive relationships between teacher training and teacher education with student achievement after controlling for other variables. Of all the teacher-level characteristics, teacher subject knowledge exhibits the highest correlation with learning achievement. Findings’ robustness tests conducted on mathematics, Urdu, and English learning outcomes scores further corroborate the reliability of the results in varying learning areas. It can be seen from the findings that variation in teacher training plays a role in causing learning inequalities in Pakistan. The current research provides evidence to the debate regarding education quality in Pakistan by stressing the need for policy measures aimed at improving teachers’ skills and competencies.